“A rima de DEUS”: como a religiosidade popular se expressa nos cordéis. - Santos, Nivaldo Belo dos (2019)
This work aims to investigate the cycle of Popular Religiosity in Cordel Literature of the Brazilian Northeast. We seek to delight in the poetry that tells in rich detail the life of these sertanejos who need that: their faith has a physical body, that their saints have characteristics similar or equal to theirs and that their religiosity has elements that identify them. The cordel literature would, in the face of popular yearning, make the Bible of popular religiosity (we will develop this idea during the exposition of this work), it is there that sermons, teachings, orders, prayers, blessings and miracles are present. involve the everyday life of this people. This study aims to investigate the relationship that people make between their religiosity and Cordel's Literature, this poetry that is often marginalized brings the story of the People told by the people, perhaps that is why, this literature has not assumed intellectual standards European countries. We divided the study into three chapters in the first one. We sought to historicize the importance of the Cordels in the context of popular culture. We did a "Makros" walk (Greek terms), where Cordel is born with Eurocentric patterns to the "micro" when it arrives in the northeast and it gains unscrupulous space that narrates facts of everyday life, political, historical, romantic and for our studies we highlight the face of the unofficial Christian religion that arises before the needs of the people, this need encompasses everything that involves the Sacred and the Profane. In the second chapter we will discuss the elements that form this popular religious culture and that are present in Cordel's Literature. Heaven and Hell, God and the Devil, the popular saviors who brought here the figure of Father Cicero and Brother Damião, we will still work the relation of the miracles present in this type of poetry. In the third chapter we will reflect the relationship between Literary Culture and Popular Religiosity as one merges with another giving space to the faith of the people and built an endemic scenario that involves religion, culture and society. This work aims not only to annalize the culture of the people through the poetry contained in the cordel booklets, but emphasizes how the people need their faith to gain concrete body and Cordel Literature will be the door through which popular faith will be spread to all.